Simultaneous Quantification of Four Compounds in Rat Plasma by HPLC–MS/MS and Its Application to Pharmacokinetic Study after Oral Administration of Pomegranate Flowers. (23rd June 2021) - Yisimayili, Zainaipuguli; Tian, Qiang; Xie, Yang; Hu, Pei; Abdulla, Rahima; Wu, Tao; Sun, Zhaolin; Chen, Mingcang; Aisa, Haji Akber; Huang, Chenggang
Abstract: Pomegranate flowers (PFs) were reported to possess various biological activities such as antidiabetic, anti-inflammatory and hepatoprotective activities, and using to treat diabetes. Although chemical constituents and pharmacological activities of PFs have been studied, unfortunately, there was no report on the pharmacokinetic profile of PFs in vivo . In this study, a selective high-performance liquid chromatography triple quadrupole tandem mass spectrometry (HPLC–QQQ–MS/MS) method was developed and validated for simultaneous quantification of four compounds (corilagin, ellagic acid, gallic acid and brevifolincarboxylic acid) in rat plasma after oral administration of PFs. The good linearity concentration ranges for the four analytes were from 2.5 to 3000 ng/mL with coefficient value R 2  > 0.99 in calibration curves. The intra- and inter-day accuracy of the four analytes was in the range of 85.33–102.50%, with relative standard deviation (RSD) of <14.81%. The stability results showed that accuracy of the four analytes was in the range of 81.88–104.74%, with RSD of <14.86%. The validation method was successfully applied to pharmacokinetic profiles of the four analytes in rats after oral administration of PFs extract. This pharmacokinetic study can provide better understanding to clarify in vivo mechanisms of PFs and may facilitate its further development as therapeutic agent.